EFL Learners of Pre-Service Teacher Programs’ Knowledge of Collocation and Their Perceptions on Collocation - Darmawan Labira; Yohanes San Salvador L. Gili; Felisitas Siano (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
This paper was aimed to find out: (1) EFL learners of pre-service teaching program’s knowledge of collocation, and (2) EFL learners of pre-service teaching program’s perception about their knowledge of collocation and on collocation teaching in EFL setting. The data was collected from EFL learners of pre-service teaching programs of IKIP Muhammadiyah Maumere in Maumere East Nusa tenggara, Indonesia. To collect the data, a multiple choice of collocation test that consisted of thirty items was administered and 9 item of questionnaires about their perception toward collocation teaching materials, collocation learning methods, and collocation teaching techniques. The findings revealed that the average percentage of EFL learners of pre-service teaching program’s collocation errors through statistical analysis using SPSS 25.0 was 51, 50% (an average of 4.85 errors per participants). It was identified that 56.30% grammatical errors (an average of 10.68 errors per participants) and 42.60% lexical errors (an average of 10.54 errors per essay) were found. This implies that the most frequently committed errors were in the grammatical category. The study also revealed that 80% of EFL learners of pre-service teaching program agreed that the role of collocation in teaching and learning vocabulary was very important. 43% of them mostly learn collocations from the course book. They agreed that the most suitable level to learn o r teach collocations are from around elementary. They learn collocation bacause It is important for language proficiency while 30% of them said that techniques do you use in learning collocations was through translating. 40% of them agreed that reading was language skill(s) would be the most effective in learning collocations. The causes their collocational errors were 43% of them agreed that there is interference from Indonesian.